Analisis Dinamika Tren Otoritas Keagamaan: Studi Kasus di Twitter Indonesia Tahun 2009-2019 - Taufik Edy Sutanto; Nur Inayah; Naila Nabiha Qonita (AI Society & STMIK Indonesia, 2024)
Religious authority refers to individuals vested with governance over religious matters, such as kiai, ulama, and ustaz within the context of Islamic faith. In the age of social media, where freedom of expression prevails, anyone can initiate discussions on various topics, including religion. However, this freedom often raises doubts about truthfulness or validity of opinions concerning religious topics because not all information originates from credible religious authorities. This study analyzes trend dynamics of religious authority in discussions about Islam on Twitter between 2009 and 2019, using Katz centrality and Laplacian centrality. According to both methods, the findings indicate that dominance in religious conversations tends not to be held by religious authorities, with the average percentage of religious authority appearances only 14.24% in Katz centrality and 12.42% in Laplacian centrality. Results of this study are intended to serve as reference for government policy-making related to religious moderation education to public.